Changes in Biomarkers of Coagulation, Fibrinolytic, and Endothelial Functions for Evaluating the Predisposition to Venous Thromboembolism in Patients With Hereditary Thrombophilia. (1st September 2020) - Li, Lei; Gao, Lixia; Wu, Xi; Wu, Wenman; Ding, Qiulan; Wang, Xuefeng
The changes in the coagulation, fibrinolytic, and endothelial functions are correlated with the pathophysiology of the thromboembolic diseases during acute illness. However, these changes in patients with hereditary thrombophilia who were not in the acute stage of venous thromboembolism (VTE) are unclear. A panel of 4 biomarkers, including thrombin–antithrombin complex (TAT), plasmin-α2-plasmin inhibitor complex (PIC), tissue-type plasminogen activator/plasminogen activator inhibitor-1 complex (t-PAIC), and soluble thrombomodulin (sTM), were assayed in 100 healthy controls and 100 patients with thrombophilia. Although significantly higher concentrations of TAT, PIC, t-PAIC, and sTM were observed in patients with thrombophilia than in healthy controls, 70 patients showed absolutely normal levels of the above 4 biomarkers. Among the other 30 patients who had at least 1 biomarker out of the corresponding reference interval, 26 of them presented elevated PIC with or without increased TAT. Except for sTM, other 3 biomarkers did not show significant differences in patients with previous VTE compared to those without. Patients with single episode of VTE had obviously lower t-PAIC than those with multiple episodes of VTE, whereas the levels of TAT, PIC, and sTM were unassociated with the number of thrombosis episodes. Most thrombophilia patients who were not in the acute stage of VTE showed normal coagulation, fibrinolytic, and endothelial functions. Thus, we were unable to show that the one-time response of this panel was clinically helpful in determining thrombosis risk in thrombophilia individuals. Future studies should focus on the dynamic monitoring during the chronic phase of VTE to offer special advantages for patients with thrombophilia.